Speaking Across Cultures: Language Variation and Communication Patterns among Migrant Students in Higher Education - Salsa Putri Aprilia Hasan Azzahro; Nateta Dwi Desilva; Rafly Aurelian Alfattah Sutiyarto; Zam Zam Rafli Putra Handoko; Lucky Prasetyo Nggalene (Yayasan Sagita Akademia Maju, 2026)
Linguistic and cultural diversity among university students creates complex communication dynamics, particularly for internal migrant students who must adapt to new social and linguistic environments. This study aimed to examine language variation among migrant students, identify the factors influencing language choice, and explore the relationship between language use and social adaptation at Universitas Pembangunan Nasional